Adrenarche and pubarche in girls with turner syndrome during growth-promoting therapy with human growth hormone - Dörr, Helmuth-Günther; Penger, Theresa; Marx, Martin; Rauh, Manfred; Oppelt, Patricia; Völkl, Thomas (BMC Endocrine Disorders, 2019)
Background: Data on adrenarche and pubarche in girls with Turner syndrome (TS) are inconsistent in the literature. Methods: The cohort consisted of 94 girls and young women with TS born between 1971 and 2001 (age range: 3.1-23.2 yrs.), who were treated with human growth hormone and regularly presented at our outpatient clinic every 4 to 6 months.The longitudinal data of all patients were ascertained retrospectively from patient charts. The data collection ended in January 2016. Adrenarche was assessed by serum DHEAS levels and pubertal status by Tanner stages. Pubarche was defined as the appearance of pubic hair (PH2), whereas spontaneous puberty was defined as Tanner stage B2. The patients were retrospectively subdivided in two groups with regard to pubertal development: group 1 (n = 21) with spontaneous puberty and group 2 (n = 70) with induced puberty. Since blood samples were not taken at every visit, we generated seven groups according to the age of the children at which the blood samples were taken: 3-5, 5-7, 7-9, 9-11, 11-13, 13-15, and 15-17 yrs. Serum DHEAS and follicle-stimulating hormone (FSH) levels were measured by chemiluminescence immunoassay and compared with those of a control group of healthy girls. Results: Adrenarche started in TS girls between 5 and 7 years. TS girls had higher DHEAS levels than the control group, with statistically significant differences in the age groups 7 to 17 years. No differences were determined between the TS girls with spontaneous puberty and those with POI. TS girls in group 2 reached the Tanner stages PH2 (p < 0.04), PH3 (p < 0.01), PH4 and PH5 (p < 0.001) markedly later than TS girls in group 1. Conclusions: The onset of adrenarche in girls with TS undergoing GH therapy does not differ from that in healthy girls. However, adrenarche is more pronounced in girls with TS. There is no difference in DHEAS levels between the TS girls with spontaneous puberty and the TS girls with primary ovarian insufficiency (POI), while the tempo of pubarche is markedly slower in the girls with POI.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Adrenarche; DHEAS; Primary ovarian insufficiency; Turner syndrome